Изменчивость питания лося (Alces alces L.) в осенне-зимний период в Березинском заповеднике - Козло, П.Г. (Вестник зоологии, 1972)
The content of stomaches was analysed in 210 elk killed during 1966—1971. In 1966—1968 37.496 of the elk food consisted of Pinus silvestris L., 46.8% — of Salix L., 6.896 — Populus tremula L., 4.296 — of Frangula alnus L., other species accounted for 4.896. In 1969—1971 consumption of Pinus silvestris by elks was almost twice as high (61.9%), «non-fodder» plants: Betula L.— (1 1.3%), Alnus glutinosa L., Picea excelsa L., etc. were eaten more often and in greater amounts. Till 1968 the elks did not eat Betula L. at all. The portion of Salix L. (Д 7.5%), Populus tremula L. (0.7%) and Frangula alnus Ь. (0.5%) in the elk food decreased correspondingly. As а result of forage reserve impoverishment апс1 changes in the elk nutrition, the physiological state of the population grew worse: accumulation of fat decreased, potential fecundity of the elk females sharply fell, infestation with endoparazites increased, growth and development of young animals, trophy qualities 0f antlers, etc deteriorated. The density of the elk population in the reservation is assumed to exceed the ultimate ecological оnе (28 individuals реr 1000 ha of the utilized area), and control of its quantity is necessary.